2008
DOI: 10.1182/blood-2008-02-139105
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic challenge unmasks a requirement for PI3Kδ in NK cell–mediated tumor surveillance

Abstract: Specific inhibitors of PI3K isoforms are currently evaluated for their therapeutic potential in leukemia. We found that BCR/ ABL ؉ human leukemic cells express PI3K␦ and therefore explored its impact on leukemia development. Using PI3K␦-deficient mice, we define a dual role of PI3K␦ in leukemia. We observed a growth-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…The well-known NK-target cell line YAC-1, which lacks MHCI expression, was used as a positive control in all experimental settings. 39 To investigate the effect of T cells, we performed in vitro T-cell cytotoxicity assays. Although no specific killing over the baseline was observed against E-myc/p53 ϩ/Ϫ tumor targets, E-myc/vav-bcl-2 tumor targets were efficiently recognized and lysed by cytotoxic T lymphocytes ( Figure 5E).…”
Section: Nk and T Cell-mediated Cytotoxicity Is Enhanced On Bcl-2 Expmentioning
confidence: 99%
“…The well-known NK-target cell line YAC-1, which lacks MHCI expression, was used as a positive control in all experimental settings. 39 To investigate the effect of T cells, we performed in vitro T-cell cytotoxicity assays. Although no specific killing over the baseline was observed against E-myc/p53 ϩ/Ϫ tumor targets, E-myc/vav-bcl-2 tumor targets were efficiently recognized and lysed by cytotoxic T lymphocytes ( Figure 5E).…”
Section: Nk and T Cell-mediated Cytotoxicity Is Enhanced On Bcl-2 Expmentioning
confidence: 99%
“…2 The genes encoding the PI3K catalytic and regulatory chains are members of multi-gene families. Historically, the p110a isoform has been the best-characterized catalytic subunit; however, it has been recently shown that the p110d isoform may play a larger role in leukemogenesis [3][4][5] and tumor surveillance than expected previously. The activation of the PI3Kd isoform does not appear to be due to genetic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this notion, Zebedin et al (45) have recently shown evidence of impaired NK cell cytotoxicity in p110␦ Ϫ/Ϫ mice on a mixed (129xC57BL/6) background. We think the discrepancy with the results published by us and others, using mice on C57BL/6 (29,36) or C57BL/10 background (28), could be due to the genetic background itself.…”
Section: Discussionmentioning
confidence: 73%